Plasticizers Increase Adhesion of the Deteriogenic Fungus Aureobasidium pullulans to Polyvinyl Chloride - Webb, Jeremy S. (American Society for Microbiology, 1999)
Initial adhesion of fungi to plasticized polyvinyl chloride (pPVC) may determine subsequent colonization and biodeterioration processes. The deteriogenic fungus Aureobasidium pullulans was used to investigate the physicochemical nature of adhesion to both unplasticized PVC (uPVC) and pPVC containing the plasticizers dioctyl phthalate (DOP) and dioctyl adipate (DOA). A quantitative adhesion assay using image analysis identified fundamental differences in the mechanism of adhesion of A. pullulans blastospores to these substrata. Adhesion to pPVC was greater than that to uPVC by a maximum of 280% after a 4-h incubation with 10(8) blastospores ml(−1). That plasticizers enhance adhesion to PVC was confirmed by incorporating a dispersion of both DOA and DOP into the blastospore suspension. Adhesion to uPVC was increased by up to 308% in the presence of the dispersed plasticizers. Hydrophobic interactions were found to dominate adhesion to uPVC because (i) a strong positive correlation was observed between substratum hydrophobicity (measured by using a dynamic contact angle analyzer) and adhesion to a range of unplasticized polymers including uPVC, and (ii) neither the pH nor the electrolyte concentration of the suspension buffer, both of which influence electrostatic interactions, affected adhesion to uPVC. In contrast, adhesion to pPVC is principally controlled by electrostatic interactions. Enhanced adhesion to pPVC occurred despite a relative reduction of 13° in the water contact angle of pPVC compared to that of uPVC. Furthermore, adhesion to pPVC was strongly dependent on both the pH and electrolyte concentration of the suspension medium, reaching maximum levels at pH 8 and with an electrolyte concentration of 10 mM NaCl. Plasticization with DOP and DOA therefore increases adhesion of A. pullulans blastospores to pPVC through an interaction mediated by electrostatic forces.